SLAs for cloud applications: agreement protocol and REST-based implementation. (2017) - Benedictis, Alessandra De; Rak, Massimiliano; Villano, Umberto
Users with critical data are still reluctant to move apps and data to commercial clouds, showing a substantial lack of trust in providers. Possible risks linked to availability, performance and security may be mitigated by the adoption of Service Level Agreements (SLAs) established among cloud service providers and their customers. This paper presents the design of services for the automatic management of cloud-oriented SLAs by means of a REST-based API. The API is exposed by an SLA Manager component that can be easily integrated into existing cloud applications, platforms and infrastructures, in order to support SLA-based cloud services delivery. Its functionalities have been designed according to an extended version of the agreement protocol state diagram proposed by the WS-Agreement standard, which takes explicitly into account negotiation, remediation and renegotiation issues and is compliant with all the active standards on security.